The clergy and the Cortes of 1361: networks and protagonists in the time of Pedro I of Portugal - Vasconcelos Vilar, Hermínia (2020)
In 1361 D. Pedro gathered Cortes in Elvas, a very uncommon place if we take in account the places chosen for these meetings. One of things most remarkable of this Cortes was the presentation of a list of grievances by the Portuguese clergy to the king. List that was, several decades after, collected in the Ordenações Afonsinas. Normally seen as a reflection of the persistence of previous problems between clergy and kings, the content and context of these grievances deserve a more detailed analysis. In this article, we intend to draw attention to the implications of the frequent presentation of grievances by the clergy to the king or pope and also to the importance of the crisis of 1355 -1356 in the first years of governance of D. Pedro.   Bibliography Sources: Handwritten sources Lisboa, ANTT - Cabido da Sé de Lamego, maço 3 de doações, cartas e mercês régias, n.º8 e 10. - Gavetas, Gaveta XIII, maço 5, nº 4.  Printed sources Chancelarias Portuguesas. D. Pedro I. Lisboa: Instituto Nacional de Investigação Científica, 1984.  Cortes Portuguesas. Reinado de D. Afonso IV (1325-1357). Lisboa: Instituto Nacional de Investigação Científica, 1982.  Cortes Portuguesas. Reinado de D. Pedro I (1357-1367). Lisboa: Instituto Nacional de Investigação Científica, 1986. COSTA, António Domingues de Sousa (ed.) – Monumenta Portugaliae Vaticana. I Súplicas dos pontificados de Clemente VI, Inocêncio VI e Urbano V. Braga/ Porto: Editorial Franciscana, 1968. Innocent VI (1352-1362). Lettres secrètes et curiales, publiées ou analysées par Pierre Gasnault. Tome III, fascicule IV. Paris: Éd. de Boccard, 1968. Livro I de Místicos de Reis, Livro II dos Reis D. Dinis, D. Afonso IV D. Pedro. Documentos para a História da Cidade de Lisboa. Lisboa: Câmara Municipal de Lisboa, 1947. LOPES, Fernão – Crónica de D. Pedro. Lisboa: Imprensa Nacional-Casa da Moeda, 2007. Ordenações Afonsinas, 2ª ed., livros I-V. Lisboa: Fundação Calouste Gulbenkian, 1998. Estudos: AMBLER, S. T. – Bishops in the Political Community of England, 1213-1272. Oxford: Oxford University Press, 2017. ARNAUT, Salvador Dias – A Crise Nacional Dos Fins Do Século XIV. I - A Sucessão de D. Fernando. Lisboa: Imprensa de Coimbra, 1960. ARRANZ DE GUZMAN, Ana – “Reconstrucción y verificación de las Cortes castellano-leonesas: la participación del clero”. En La España Medieval 13 (1990) pp. 33-132. CAETANO, Marcello – História Do Direito Português. Fontes- Direito Público (1140-1495), 2a ed. Lisboa: Editorial Verbo, 1985. CASTRO, José Osório da Gama e – Diocese e Districto da Guarda. Porto: [s.e.] 1902. COELHO, Maria Helena da Cruz – “O arcebispo D. Gonçalo Pereira: um querer, um agir”. in IX Centenário da Dedicação da Sé de Braga. Congresso Internacional. Actas, volume II/1 - A Catedral de Braga na História e na Arte (séculos XII-XIX). Braga: Universidade Católica Portuguesa, Faculdade de Teologia, Cabido Metropolitano e Primacial de Braga, 1990, pp. 389-462. COSTA, Adelaide Millán – “Comunidades urbanas de senhorio eclesiástico; a divergente experiência das Cidades do Porto e de Braga”. in Estudos em Homenagem ao Prof. Dr. José Marques. Vol. I. Porto: FLUP, 2006, pp. 77-85. COSTA, Adelaide Pereira Millán da, “As mulheres de D. Pedro I. Branca de Castela, Constança Manuel e Inês de Castro”. in Menino, Vanda Lourenço; COSTA, Adelaide Lopes Pereira Millán – A rainha, as infantas e a aia: Beatriz de Castela, Branca de Castela, Constança Manuel, Inês de Castro. Lisboa: Círculo de Leitores, 2012 CRUZ, António – “Os bispos senhores da cidade. II – de D. Pedro Salvadores a D. Vasco Martins”. in PERES, Damião e CRUZ, António (eds.) – História da cidade do Porto. Vol. I. Porto: Portucalense Editora, 1962, pp. 184-248. DENTON, J. H. – “The Making of the “Articuli Cleri” of 1316”. The English Historical Review 101.400 (1986), pp. 564–595. DIAZ IBÁNEZ, Jorge; FARELO, Mário – “Pedro Gómez Barroso, O jovem”. in FONTES, João Luis (dir); GOUVEIA, António Camões, ANDRADE, Maria Filomena e FARELO, Mário (coord.) – Bispos e Arcebispos de Lisboa. Lisboa: Livros Horizonte, 2018, pp. 345-351. DOMINGUES, José – As Ordenações Afonsinas: três séculos de direito medieval [1211-1512]. Sintra: Zéfiro, 2008. EUBEL, Conradus – Hierarchia Catholica Medii Aevi sive Summorum Pontificum, S.R.E. Cardinalium, Ecclesiarum Antistitum Series: ab Anno 1198 usque ad annum 1431 perducta:et Documentis tabularii praesertim Vaticani collecta, digesta. Monasterii, 1935-1978. FERREIRA, Monsenhor J. Augusto – Memórias Archeológico-Históricas da cidade do Porto. Braga: Livraria Cruz, 1923. FREITAS, Eugénio Cunha e – “Os bispos senhores da cidade. III- de D. Pedro Afonso a D. Gil Alma”.  in PERES, Damião e CRUZ, António (eds) – História da cidade do Porto. Vol. I. Porto: Portucalense Editora, 1962, pp. 249-279. GOMES, Jesué Pinharanda – História da Diocese da Guarda. Braga: [edição do autor] 1981. HOMEM, Armando Luís de Carvalho – O Desembargo Régio (1320-1433). Porto: Instituto Nacional de Investigação Científica, Centro de História da Universidade do Porto, 1990. HOMEM, Armando Luís de Carvalho – “Subsídios para o estudo da administração central no reinado de D. Pedro I”. in HOMEM, Armando Luís de Carvalho – Portugal nos finais da Idade Média: Estado, Instituições, Sociedade Política. Lisboa: Livros Horizonte, 1990, pp. 63-107. JONES, W. R. – “Bishops, Politics, and the Two Laws: The Gravamina of the English Clergy”. Speculum 41:2 (1966), pp. 209–245. LEITÃO, André de Oliveira – “Lourenço Rodrigues (ou Lourenço Martins de Barbudo)”. in FONTES, João Luis (dir); GOUVEIA, António Camões, ANDRADE, Maria Filomena; FARELO, Mário (coord.) – Bispos e Arcebispos de Lisboa. Lisboa: Livros Horizonte, 2018, pp. 329-344. LEITÃO, André de Oliveira; NORTE, Armando – “Vasco Rodrigues”. in FONTES, João Luis (dir); GOUVEIA, António Camões, ANDRADE, Maria Filomena; FARELO, Mário (coord.) – Bispos e Arcebispos de Lisboa. Lisboa: Livros Horizonte, 2018, pp. 361-379. LINEHAN, Peter – At the Edge of Reformation: Iberia before the Black Death. New York: Oxford University Press, 2019. LINEHAN, Peter - The Spanish Church and the Papacy in the Thirteenth Century. Cambridge: Cambridge University Press, 2005. LOUREIRO, Sara – “O conflito entre D. Afonso IV e o infante D. Pedro (1355-1356)”. Cadernos do Arquivo Municipal, 1ª série, 7 (2003), pp. 8-62. MARQUES, A. H. de Oliveira – Portugal na Crise dos séculos XIV e XV. Vol. IV. Nova História de Portugal. Dir. Joel Serrão e A. H. de Oliveira Marques. Lisboa: Estampa, 1987. MARQUES, A. H. de Oliveira; DIAS, João Alves – Atlas Histórico de Portugal e do Ultramar Português. Lisboa: Centro de Estudos Históricos, 2003. MARQUES, José – “D. Afonso IV e as jurisdições senhoriais”. in Actas das II Jornadas Luso-Espanholas de História Medieval. Vol. IV. Porto: INIC, 1990, pp. 1527-1566. MARQUES, José – “Igreja e poder régio”. in A Génese do Estado Moderno no Portugal Tardo-medievo. Ciclo de conferências. Lisboa: Universidade Autónoma de Lisboa, 1999, pp. 217-256. MACHADO, J.T. Montalvão – Itinerários de El-Rei D. Pedro (1357-1367) Lisboa: Academia Portuguesa de História, 1978. MORUJÃO, Maria do Rosário – “Bispos em tempo de guerra: os prelados de Coimbra na segunda metade do século XIV”. in A Guerra e a sociedade na Idade Média. Actas das VI Jornadas Luso-Espanholas de Estudos Medievais, 2 vols. Coimbra: Sociedade Portuguesa de Estudos Medievais, 2009, vol. II, pp. 539-550. MUXAGATA, Ana Filipa Coelho – A Corte de D. Pedro I (1320-1367). Lisboa: Universidade de Lisboa, 2019. Dissertação de Mestrado. O’CALLAGHAN, Joseph – “The Ecclesiastical Estate in the Cortes of Leon-Castille, 1252-1350”. The Catholic Historical Review, 67.2 (1981), pp. 185-213. PIMENTA, Cristina – D. Pedro I. Rio de Mouro: Círculo de Leitores, 2005. SARAIVA, Anísio Miguel de Sousa - “O processo de inquirição do espólio de um prelado trecentista: D. Afonso Pires, bispo do Porto (1359-1372).” Lusitania Sacra, 2ª série, 13-14 (2001-2002), pp. 197-228. SOUSA, Armindo de – As Cortes Medievais Portuguesas (1385-1490), 2 vols. Porto: Instituto Nacional de Investigação Científica, 1990. SOUSA, Bernardo Vasconcelos e - D. Afonso IV. Lisboa: Círculo de Leitores, 2005. SOUSA, Bernardo Vasconcelos e – “A Guerra Civil de 1355”. in A Guerra e a sociedade na Idade Média. Actas das VI Jornadas Luso-Espanholas de Estudos Medievais. Vol. II. Coimbra: Sociedade Portuguesa de Estudos Medievais, 2009, pp. 393-407. TABBAGH, Vincent – Les Évêques dans le Royaume de France au XIVe Siècle. Dijon: Éditions universitaires de Dijon, 2015. VILAR, Hermínia Vasconcelos – “Episcopal appointments and royal power: theory and practice of an unwritten privilege in medieval Portugal”. Imago Temporis. Medium Aevum 11 (2017), pp. 233-254. VILAR, Hermínia Vasconcelos – “No tempo de Avinhão: Afonso IV e o episcopado em meados de Trezentos”. Lusitania Sacra. 2ª série, 22 (2010), pp. 149-168. ZUTSHI, Patrick – “Petitions to the Pope in the Fourteenth Century”. in ORMROD, W. Mark, et al. (ed.) – Medieval Petitions: Grace and Grievance. Suffolk: Boydell & Brewer, 2009, pp. 82-98.